Electron ionization mass spectra of phosphorus-containing heterocycles. II. 1,2,3,4,4a,5,6,7,8,8a-decahydro-1,3,2-benzodiazaphosphinine 2-oxides - Martiskainen, Olli; Juhász, Márta; Zalán, Zita; Fülöp, Ferenc; Pihlaja, Kalevi (Rapid communications in mass spectrometry, 2006)
The electron ionization mass spectra of cis‐ and trans‐fused 1,2,3,4,4a,5,6,7,8,8a‐decahydro‐1,3,2‐benzodiazaphosphinine 2‐oxides (1–17) were recorded, and the fragmentation pathways were established and compared with those of 1,4,4a,5,6,7,8,8a‐octahydro‐2H‐3,1,2‐benzoxazaphosphinine 2‐oxides. In general, the mass spectral behaviors of the isomeric compounds were very similar and it was mostly impossible to differentiate them from each other on the basis of the relative abundances of their characteristic fragment ions. The compounds in which R2 = Ph or OPh exhibited a series of common fragments, e.g. [R2H]+, R2PONHR1(3)+, [M–C3H7]+ and [M–C4H9]+, the latter two ions being present in the spectra of only two of the derivatives with an N(CH2CH2Cl)2 substituent on the P atom. When R2 = Ph, numerous other alkyl radicals, alkenes and a cycloalkane were also ejected and these compounds also lost NH2, NH3, CH3N, CH4N or CH3NH2. The compounds with an N(CH2CH2Cl)2 substituent on the P atom most closely resembled their 3,1,2‐O,N,P analogs in respect of the dominant role of this substituent. Copyright © 2006 John Wiley & Sons, Ltd.